Cross-linking affects cellular condensation and chondrogenesis in type II collagen-GAG scaffolds seeded with bone marrow-derived mesenchymal stem cells - Vickers, Scott; Gotterbarm, Tobias; Spector, Myron (Journal of orthopaedic research, 2010)
The formation of cartilaginous tissue by chondroprogenitor cells, whether in vivo or in vitro, appears to require a critical initial stage of “condensation” in which intercellular space is reduced through an aggregation of cells, leading to development of cell-to-cell junctions followed by chondrocytic differentiation. The objective of this study was to investigate the association of aggregation (condensation) of mesenchymal stem cell (MSCs) and chondrogenesis in vitro.
Gesehen am 05.09.2023